The Seventh Power - Hancock, Kevin (Ascent Audio, 2020)
A corporate executive loses his voice and discovers a new pathway to organizational excellence built on the premise of dispersed power and shared leadership.
Online resource; Title from title page (viewed February 25, 2020)
Keywords: Business; Affaires; businesses (business enterprises); Audiobooks